FORMATION OF A HEALTHY LIFESTYLE BASED ON THE CLASSIFICATION OF PHYSICAL EDUCATION OF PRIMARY SCHOOL CHILDREN (Scientific journal of the Fergana State University, 2024)
This article highlights such information as the inclusion of control exercises in the sphere of pedagogical control of physical fitness of younger schoolchildren, characterizing the level of development of basic physical qualities: speed, dexterity-strength, endurance, coordination abilities, flexibility and strength.